Vertical Integration of Grain Producer Market with Rice Retail Market in Indonesia - aryani, desi (Jurnal Manajemen Teknologi, 2012)
This paper aims to analyze the vertical integration of markets between producers market grain rice with a retail market in Indonesia. Results of analysis useful for government to review whether the price received by farmers is quite feasible when viewed from the price of rice sold to consumers. The data used are secondary data from monthly data for average price of rice retail and average prices of grain producers in Indonesia. Monthly data from January 2000 to December 2008 is the time series data and analyzed with a model of Vector Autoregression (VAR). The results showed that the price movements of grain producers and rice consumers in Indonesia have a similar direction, but the price of grain producers more volatile than rice consumers. Grain producers market has not fully integrated with the rice retail market in Indonesia. In the short term grain producers market influenced by rice consumers market but it does not vice versa. Government intervention is needed in the grain producers market. If the grain producers market is fully integrated with rice retail market, it will mean changes in the retail price of rice is also followed by changes in the price of grain producers with the same direction.How to cite:Aryani, D. (2012). Vertical Integration of Grain Producer Market with Rice Retail Market in Indonesia. Jurnal Manajemen Teknologi, 11(2), 225-238.Â doi:10.12695/jmt.2012.11.2.7